Zoledronic acid induces ferroptosis by reducing ubiquinone and promoting HMOX1 expression in osteosarcoma cells - Ren, Tianhao; Huang, Ju; Sun, Wei; Wang, Guangze; Wu, Yuwen; Jiang, Zewei; Lv, Yingshuai; Wu, Guang; Cao, Jiawei; Liu, Min; Gu, Haihua (Frontiers in Pharmacology, 2023)
Aims: Ferroptosis plays important roles in tumorigenesis and cancer therapy. Zoledronic acid is known to inhibit the activity of farnesyl pyrophosphate synthase, a key enzyme in the mevalonate pathway. We examined whether zoledronic acid can inhibit the growth of osteosarcoma cells by inducing ferroptosis. Methods: Cell viability was analyzed by using CCK8 reagent and counting cells with trypan blue exclusion. Ferroptosis markers including lipid peroxide and PTGS2 expression were examined by flow cytometry, western blot, and quantitative PCR analyses. Cellular ubiquinone content was determined using high performance liquid chromatography. Ferrostatin-1 and RSL3 were used as the ferroptosis inhibitor and inducer respectively. Results: Zoledronic acid treatment decreased cell viability and promoted the increase in lipid peroxide content and PTGS2 expression. Addition of ferrostatin-1 reverted these effects of zoledronic acid on osteosarcoma cells, supporting a role of zoledronic acid in inducing ferroptosis. Mechanistically, zoledronic acid significantly decreased ubiquinone, a metabolite of the mevalonate pathway. Treating cells with exogenous ubiquinone prevented zoledronic acid- induced ferroptosis and decrease in the growth of osteosarcoma cells. In addition, zoledronic acid enhanced the expression of HMOX1, whereas knockdown of HMOX1 inhibited the zoledronic acid-induced increase in lipid peroxide level and decrease in cell growth. Finally, zoledronic acid together with RSL3 significantly enhanced the inhibitory effect on the growth of osteosarcoma cells. Conclusion: Our results indicate that zoledronic acid induces ferroptosis by decreasing ubiquinone content and promoting HMOX1 expression in osteosarcoma cells. Zoledronic acid together with ferroptosis inducer may be a promising new strategy for the treatment of osteosarcoma.